Pengembangan Digital Flipbook Terintegrasi Mind Map (DFM) Untuk meningkatkan Pemahaman Konsep Siswa Kelas XI pada Materi Sistem Pencernaan di SMA - Fauzianti, Windi; Tambunan, Efrida Pima Sari (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to develop digital learning media in the form of flipbooks integrated with mind mapping to improve the understanding of concepts of grade XI students in the digestive system material at SMA Negeri 2 Percut Sei Tuan. This study uses the Research and Development (R&D) method with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. At the development stage, the media was validated by material and media experts who showed results of 97.77% with the criteria of